Trends of Humane Literacy in EFL Assessment as an Alternative for Future Learning: A Systematic Review - Shilvy Inayatillah; Nurul Syafika; Siti Drivoka Sulistyaningrum (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Traditional EFL assessment prioritises cognitive and linguistic outcomes, neglecting the affective, ethical, and sociocultural dimensions essential to holistic language development. This study examines publication trends and thematic patterns of humane literacy integration in EFL assessment (2013–2023). Following PRISMA guidelines, five databases (Google Scholar, ERIC, Lens.org, Connected Papers, Open Knowledge) were systematically searched; 23 peer-reviewed articles met inclusion criteria and were analyzed through thematic synthesis appraised using the CASP qualitative checklist. Publication peaks in 2018 (n = 7) and 2023 (n = 4) reflect sustained scholarly interest. Thematic synthesis identified five core humane literacy value factors: comprehensive literacy skills integration, cultural and contextual awareness, critical thinking and ethical reasoning, creativity and innovation, and collaboration and communication. Findings propose "humanistic assessment literacy" as an expanded framework for EFL teachers and advocate portfolio assessment, culturally responsive rubrics, and peer evaluation as congruent classroom practices. Curriculum reform and targeted teacher training are recommended to bridge humanistic ideals and institutional assessment policy.